2012
DOI: 10.1002/rcm.6246
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantification of microcystins and nodularin in aerosol samples using high‐performance liquid chromatography/negative electrospray ionization tandem mass spectrometry

Abstract: The method was applied to ten aerosol samples from the Venice Lagoon. In these samples, trace concentrations of MC-LA ranging between 90 fg m(-3) and 706 fg m(-3), MC-LF between n.d. and 369 fg m(-3) and MC-LW between n.d. and 262 fg m(-3). This is the first study to quantify the cyanotoxins in Venetian aerosol samples using the HPLC/(-)ESI-MS/MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 42 publications
1
29
0
1
Order By: Relevance
“…Negative ionization mode by MALDI and ESI presented low absolute intensities but also low background and therefore provided suitable S/N ratios. According to other authors [19][20][21]44], as shown Table S1 of supplementary data, the analysis of MCs containing no Arg residue such as MC-LA, -LF, -LW and -LY presented high sensitivity in negative ionization mode.…”
Section: Throughput Analysis (Direct Maldi and Esi Analysis)mentioning
confidence: 97%
See 1 more Smart Citation
“…Negative ionization mode by MALDI and ESI presented low absolute intensities but also low background and therefore provided suitable S/N ratios. According to other authors [19][20][21]44], as shown Table S1 of supplementary data, the analysis of MCs containing no Arg residue such as MC-LA, -LF, -LW and -LY presented high sensitivity in negative ionization mode.…”
Section: Throughput Analysis (Direct Maldi and Esi Analysis)mentioning
confidence: 97%
“…Typically, the positive ionization mode is the most usually ionization mode employed. Additionally, electrospray (ESI) recorded in negative ion mode has recently been applied to the analysis of MCs [19][20][21]. In order to have faster methods for toxin analysis: ultra-high performance liquid chromatography (UHPLC) [22][23][24], on-line solid phase extraction (SPE) [25][26][27][28] and direct analysis without prior extraction [29,30] and chromatographic separation [31,32] have been implemented in several works.…”
Section: Introductionmentioning
confidence: 99%
“…The negative mode of ionization usually is not considered for analytical purposes. Recently, Gambaro et al (2012) applied successfully a negative ionization electrospray sensitive method to aerosol samples, using a triple quadrupole MS spectrometer equipped with a turbo V source. Using such experimental conditions, the negative full-scan mass spectra for MC-RR-YR-shown the prevalent presence of [M-2H] 2À .…”
Section: Occurrence and Distribution Of Microcystinsmentioning
confidence: 99%
“…Single [MþH] þ and double charged [Mþ2H] 2þ ions are frequently observed in the positive mode, especially for variants containing basic arginine residues, such as MC-RR (Dörr et al, 2010). However, recently, Dörr et al (2011) presented an extensive study with the mass spectra characterization of several microcystins after negative electrospray ionization and Gambaro et al (2012) presented a negative ionization electrospray quantitative method, using liquid chromatography coupled to a triple quadrupole, applied to aerosol samples from Venice Lagoon, reaching detection limits of 1 ng/L. This work presents the development and application of an analytical LC/ESI/MS 2 ion trap method, using the negative ionization mode, which can be used as a sensitive and accurate tool for the characterization of environmental and health risks due to cyanotoxins.…”
Section: Introductionmentioning
confidence: 97%
“…Up to now, chromatographic techniques with different detection principles such as, UV absorption and mass spectrometry are prior options to identify the variants and quantify the concentrations of MCs in aquatic environment [7][8][9]. Capillary electrophoresis has also been applied to the separation and anal-ysis of MCs [10].…”
Section: Introductionmentioning
confidence: 99%